The Effect of Corporate Social Responsibility as a Moderating Variable on Determinants of Banking Profitability in Indonesia - Pungkisiwi, Yunia; Hermanto, Hermanto (LPPM Institut Pendidikan Nusantara Global, 2024)
This study examined the effect of Corporate Social Responsibility (CSR) as a moderating variable on determinants of a bank’s profitability listed in the Indonesia Stock Exchange (IDX). This study used secondary data from banking annual reports listed in IDX during 2018-2021, with a total of 100 data from 25 banking companies that met the purposive sampling criteria. The data were analysed using moderated regression analysis with STATA software. This study found that simultaneously, Non-performing Loan (NPL), Good Corporate Governance (GCG), Third Party Funds (TPF), and Cost Efficiency have a significant impact on profitability. While individually, GCG has a significant negative effect, NPL has an insignificant negative effect, Third Party Funds has a significant positive effect, and Cost Efficiency has a significant negative effect on profitability. Furthermore, this study found that CSR has a positive moderating effect on the relationship between TPF and profitability, but CSR has a negative moderating effect on the relationship between Cost Efficiency and profitability. On the other hand, CSR was unable to moderate the relationship of NPL and GCG to profitability. This study contributes to the literature by suggesting the implementation of CSR not only as a compliance to regulation but also as a strategy to increase banking financial performance.